Rediscovery of the Neotropical water scavenger beetle Protistolophus spangleri Short with notes on its habitat and behavior (Coleoptera: Hydrophilidae: Hydrophilinae) - Short, Andrew Edward Z.; Santana, Larissa; Benetti, Cesar J.; Hamada, Neusa (Zootaxa, 2020)
The water scavenger beetle genus Protistolophus Short contains a single species, P. spangleri Short, 2010, known from southern Venezuela. The genus was hitherto known only from a single partly-incomplete male specimen, making it one of the rarest and most poorly known aquatic hydrophilid genera in the world. Only one other New World aquatic hydrophilid genus, the Ecuadorian cave endemic Troglochares Spangler, is known from a single specimen or locality. In a phylogenetic analysis of the Hydrophilini based on adult morphology, the genus Protistolophus was resolved as the sister taxon to the remaining genera of the tribe, implying it is an ancient and possibly relict lineage—it possesses a very unusual combination of characters, including a very weakly developed mesoventral keel. It was the only genus not included in a recent molecular phylogeny of the Hydrophilini as no suitable material was available for DNA (Toussaint et al. 2017).